"To Enter the Core of Death": listening to the rhythm of death in água viva and the passion according to g.h. alongside the psychoanalytic clinic. Issue 2 (4th March 2023) - Aleksandrowicz, Marta
Abstract: This essay explores figurations of death in Lispector's The Passion According to G.H. and Água Viva . As the other side of life, death in these novels is tied to the work of the unconscious desire that introduces generative rupture to the narrators' experience of being, thinking, and writing. In making one wander at the limits of thought, language, and being, death also signals the encounter with femininity which leads to the disintegration of the human montage. While in Água Viva the encounter with death unfolds through the instant – as the fleeting yet irreducible nowness – in The Passion it manifests through a gustatory and aural encounter with the mute cockroach and the absent maid's mural. Along the way, the essay explores the specific savoir coming from death in Lispector's novels alongside the clinic of psychoanalysis, primarily the recent work of the Freudian School of Quebec that has placed special focus on the links between the death drive and the aesthetic experience. I bring Lispector's novels into conversation with psychoanalysis to propose that Clarice's writing – just like the psychoanalytic clinic – fundamentally arises from the desire to uphold the unsayable dimension of death whose creative unfolding enables new modes of being, hearing, and thinking in – and with – the world. Indeed, in Clarice's novels, to be on the side of writing is to be on the side of death that is both the herald of writing and the ravaging reverberation of the force of writing itself.